1995
DOI: 10.1002/jat.2550150311
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in the respiratory tract of mice exposed to ten families of airborne chemicals

Abstract: The objective of this experimental work was to identify and compare the histopathological changes induced in the respiratory tract of Swiss mice exposed to repeated inhalation (4, 9 or 14 days) at typical concentrations of RD50, 0.3 x RD50 and 3 x RD50 of airborne chemicals. These substances were selected from ten chemical families: aldehydes, organic acids, alcohols, ketones, ethers, aromatic hydrocarbons, halogenated aromatic hydrocarbons, inorganic bases, amines and isocyanates. These experiments showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…1 The Expert Panel reviewed newly available studies since that assessment along with updated frequency and concentration of use information. 212 The Expert Panel determined to not reopen this safety assessment and confirmed that diisopropylamine is safe as a cosmetic ingredient when used in products that do not contain N -nitrosating agents.…”
Section: Resultsmentioning
confidence: 99%
“…1 The Expert Panel reviewed newly available studies since that assessment along with updated frequency and concentration of use information. 212 The Expert Panel determined to not reopen this safety assessment and confirmed that diisopropylamine is safe as a cosmetic ingredient when used in products that do not contain N -nitrosating agents.…”
Section: Resultsmentioning
confidence: 99%
“…We found that absorption of inhaled PAL (% absorbed) by both rat and mouse decreased at the 100-ppm exposure concentration relative to the 1-and 10-ppm exposures. Zissu (1995) reported the observation that inhalation exposure to PAL ( ¹ 25 and 88 ppm) results in a decrease in respiratory rate in the Swiss mouse. Respiratory rate was not measured in the current studies, and the amount of PAL inhaled was assumed to be the theoretical amount inhaled during the 6-h exposure based on a normal respiratory rate.…”
Section: Discussionmentioning
confidence: 97%
“…2 Zissu (1995) 2 Study well documented, meets generally accepted scientific principles, acceptable for assessment…”
Section: Registrants' Reliability Evaluationsmentioning
confidence: 99%